Safe and successful bone marrow biopsy: An anatomical and CT‐based cadaver study. Issue 10 (11th July 2014) - Konda, Bhavana; Pathak, Swati; Edwin, Inga; Mishall, Priti; Downie, Sherry A.; Olson, Todd R.; Reed, Louis J.; Friedman, Ellen W.
<x xml:space="preserve">Abstract</x> Bone marrow biopsy is generally a safe procedure. However, infrequently the procedure is associated with serious injuries that are attributed to inadvertent needle penetration of the iliac bone's inner cortex. An evidence‐based approach to needle orientation during iliac crest biopsy does not exist. In our study, the posterior to anterior path of the bone marrow needle from the posterior superior iliac spine (PSIS) was studied in human cadavers in two orientations: (1) perpendicularly to the coronal plane (the perpendicular approach) and (2) laterally toward the ipsilateral anterior superior iliac spine (ASIS) (the lateral approach). The biopsy needle was deliberately advanced through the inner ilial cortex in both approaches. Dissections and imaging studies were done to identify the relationship of the penetrating needle to internal structures. Both approaches begin with a perpendicular puncture of the outer cortex at the PSIS. The perpendicular approach proceeds anteriorly whereas in the lateral approach the needle is reoriented toward the ipsilateral ASIS before advancing. The lateral approach caused less damage to neurovascular structures and avoided the sacroiliac joint compared to the perpendicular approach. This procedure is best done in the lateral decubitus position. Proper use of the lateral approach should obviate many of the complications reported in the literature. Am. J. Hematol. 89:943–946, 2014. © 2014 Wiley Periodicals, Inc.